Disabled is a bona fide component of the Abl signaling network. - Song, J.K.; Kannan, R.; Merdes, G.; Singh, J.; Mlodzik, M.; Giniger, E. (Development, 2010)
Abl is an essential regulator of cell migration and morphogenesis in both vertebrates and invertebrates. It has long been speculated that the adaptor protein Disabled (Dab), which is a key regulator of neuronal migration in the vertebrate brain, might be a component of this signaling pathway, but this idea has been controversial. We now demonstrate that null mutations of Drosophila Dab result in phenotypes that mimic Abl mutant phenotypes, both in axon guidance and epithelial morphogenesis. The Dab mutant interacts genetically with mutations in Abl, and with mutations in the Abl accessory factors trio and enabled (ena). Genetic epistasis tests show that Dab functions upstream of Abl and ena, and, consistent with this, we show that Dab is required for the subcellular localization of these two proteins. We therefore infer that Dab is a bona fide component of the core Abl signaling pathway in Drosophila.